Gender, writing, spectatorships : evenings at the theatre, opera, and silent screen in late nineteenth-century Italy and beyond - Mitchell, Katharine (New York : Routledge, 2021)
"This monograph examines Italian women as protagonists and consumers of literature, theatre, opera, and film. Using personal writing, journalism, and canonical texts, it analyses female performance and women's responses"--
Includes bibliographical references and index.
Keywords: Italian literature -- 19th century -- History and criticism; Italian literature -- Women authors; Italian literature -- 20th century -- History and criticism; Women in the performing arts -- Italy -- History -- 19th century; Women in the performing arts -- Italy -- History -- 20th century; Women and the arts -- Italy -- History -- 19th century; Women and the arts -- Italy -- History -- 20th century; Feminist theory